Computer Network Information Security Monitoring System Based on Big Data Era - Sun, Yu; Liu, Xiaorong; Shen, Xiaoli (Security and communication networks, 2022)
With the rapid advancement of society and the level of programming and the rapid development of computer technology, networking and information are playing an increasingly important role in the social life of the masses. Creating and developing a network information security monitoring system have become one of the most important ways to keep a computer running smoothly. Traditional information security systems cannot adapt to the ever-changing network environment. If only relying on it to maintain network security, it will be far from effective monitoring and defense. Based on the theory of network information security, this study analyzes the characteristics of network information and the information security monitoring technology at the current stage. Based on the background of big data era, a new type of computer network information security monitoring system is proposed. This system is compared with the traditional network information security monitoring system, and the performance and stability of the system are investigated, respectively. The experimental data show that the network information security monitoring system designed in this study can achieve more than 99% detection rate of external attacks in a network environment with a background traffic of 10M. Its false alarm rate is lower than 4%, and the false alarm rate is lower than 7%. The qualitative mean reaches 93.02%, indicating its good monitoring accuracy and stability. By popularizing it in the current network environment, it can effectively identify and defend information attacks and maintain the development of network information security.